Transcriptomics yields valuable information regarding the response mechanisms of Chinese Min pigs infected with PEDV - Li, Huihui; Zhou, Chunxiang; Zhang, Meimei; Yuan, Na; Huang, Xiaoyu; Xiang, Jiaojiao; Wang, Lixian; Shi, Lijun (Frontiers in Veterinary Science, 2023)
Porcine epidemic diarrhea virus (PEDV) causes the PED, a highly infectious disease, which has resulted in huge economic losses for the pig industry. Until now, the pathogenic and immune response mechanism had been not particularly clear. The purpose of this study was to investigate the pathogenic and immune responses of pigs infected with PEDV. In this study, the infected Min piglet model was created, and the PEDV standard curve was constructed. The phenotypes of Min piglets infected with PEDV showed that the viral copy numbers and jejunal damage had significant differences between death and resistance groups. We also observed the transcriptome of jejunum, and the DE analysis observed 6,585 DE protein-coding gene (PCGs), 3,188 DE long noncoding RNAs (lncRNAs), and 350 DE microRNA(miRNAs), which were mainly involved in immune response and metabolic pathways. Further, the specific expressed molecules for each group were identified, and 99 PCGs, 110 lncRNAs, and 51 miRNAs were included in the ceRNA-regulated networks. By weighted gene coexpression network analysis (WGCNA) and transcription factors (TFs) prediction, 27 significant modules and 32 significant motifs (E-value < 0.05) annotated with 519 TFs were detected. Of these TFs, 58 were DE PCGs. In summary, the promising key PCGs, 2 lncRNAs, and miRNAs related to the pathogenic and immunological response of pigs infected with PEDV were detected and provided new insights into the pathogenesis of PEDV.